2000
DOI: 10.1097/00005373-200004000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatographic Classification of Pancreatic Ductal Injuries Caused by Blunt Injury to the Pancreas

Abstract: This classification system for pancreatic ductal injuries may facilitate the selection of appropriate therapeutic modalities for patients with blunt pancreatic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 9 publications
0
34
0
4
Order By: Relevance
“…A retrospective study performed by a Japanese group [16], analyzing the treatment of pancreatic lesions according to preoperative ERCP findings, revealed a similar conclusion [16]. These authors suggest that patients with radiographically normal ducts or with branch injuries which do not leak can be treated conservatively, while branch injuries with leaks into the retroperitoneal space require surgical drainage, and disruption of the major pancreatic duct also necessitates surgical repair.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A retrospective study performed by a Japanese group [16], analyzing the treatment of pancreatic lesions according to preoperative ERCP findings, revealed a similar conclusion [16]. These authors suggest that patients with radiographically normal ducts or with branch injuries which do not leak can be treated conservatively, while branch injuries with leaks into the retroperitoneal space require surgical drainage, and disruption of the major pancreatic duct also necessitates surgical repair.…”
Section: Discussionmentioning
confidence: 89%
“…ERCP is an elegant tool in assessing the integrity of the pancreatic duct. Additionally, ERCP offers the possibility for minimally invasive therapeutic interventions, like ductal stenting, especially in cases of partial ductal rupture [16, 17]. However, ERCP and ERCP-assisted interventions may be useful in the conservative treatment of ductal injuries, but as primary diagnostic tools in the emergency situation, they are often not available or too time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic renal failure may be a risk factor, and contrast medium leaking into the retroperitoneal space is another one. When contrast medium has leaked into retroperitoneal space or even into peritoneal cavity, the injury is more serious and operation is suggested [18]. Stenting may delay operation.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, an early ERP group (<72 h) was found to have significantly less pancreas-related complications than a later ERP group (>72 h) [10]. Positive results of stent implantation in cases of pancreatic injuries involving both children and adults have been reported [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Table 3. Classification of pancreas injuries by Takishima et al [17] Degree Description I Radiographic normal DP II Injuries to the junction of the DP a Contrast medium is inside the parenchyma b…”
Section: Discussionmentioning
confidence: 99%